Sports theology : playing inside out - Smith, Greg S. (Indianaopolis, Ind. : Dog Ear Publishing, 2014)
Sports Theology: Playing Inside Out, proposes that the highest level of athletic or personal performance is achieved by utilizing our God-given gifts. Although it is true that athletes can benefit from psychological and physical techniques, athletic potential is grounded in the original athleticism they are given by God. God encourages us to develop and maximize the gifts he has given us. Performance then is related to one's ability to understand, develop and act on these gifts. Sports theology does not conflict with, nor disregard, sports psychology, but rather sees sports theology as being more primary. Although it is true that psychology is a major part of who we are and affects our choices and behavior, it is not more powerful than our spirituality. Christianity holds that man is made in the image of God, which is our original state of perfection and is the foundation upon which all things fall. It is in relationship to this original condition that we can be all that we can be.
Keywords: Sports -- Religious aspects -- Christianity; Theology, Practical; Sports -- Religious aspects -- Christianity; Theology, Practical